Less invasive HeartMate 3 left ventricular assist device implantation - Schmitto, Jan D; Krabatsch, Thomas; Damme, Laura; Netuka, Ivan (Journal of thoracic disease, 2018)
Background: The novel HeartMate 3 (Abbott, Chicago, IL, USA) left ventricular assist device (LVAD) was worldwide first implanted by Prof. Schmitto and his team in 2014 at the Hannover Medical School, Germany and received CE Mark approval in October, 2015 following completion of a clinical trial. Methods: Although HeartMate 3 implantation in the clinical trial was restricted to conventional sternotomy, the small size of the pump allows for less-invasive implantation, generally associated with less trauma and reduced perioperative complication rates. Herein we describe our first experiences with a less-invasive implantation of the HeartMate 3 using an upper hemi-sternotomy combined with anterior lateral thoracotomy approach. Results: Results demonstrate the feasibility of this novel, less invasive technique for HeartMate 3 LVAD implantation with diminished surgical trauma, less postoperative bleeding, maintenance of the chest stability, reduced need of blood product transfusion and earlier recovery. Conclusions: The results of our study indicate that less-invasive implantation of the HeartMate 3 is technically feasible and offers several benefits for surgical outcome and may become the standard of care for LVAD implantation techniques.